Sill to surface: Linking young off-axis volcanism with subsurface melt at the overlapping spreading center at 9°03′N East Pacific Rise - Waters, C L; Sims, K W W; Klein, E M; White, S M; Reagan, M K; Girard, G (Earth and Planetary Science Letters, 2013)
No young, off-axis, mid-ocean ridge lavas have yet been directly linked to underlying off-axis melt bodies. In this study, we present new measurements of 238U–230Th–226Ra–210Pb isotope compositions for a suite of lavas from the overlapping spreading center (OSC) at 9°03′N on the East Pacific Rise (EPR). These lavas span a large range of compositions, from basalt to dacite, and include both axial and off-axis samples recovered from a prominent, axis-parallel pillow ridge and a flat-topped seamount that overlie the westernmost extent of a 4-km-wide melt lens (Kent et al., 2000). We report 210Pb excesses in axial basalts and basaltic andesites, which we suggest results from gas-magma fractionation of 222Rn from 226Ra beneath dacite magmas. In addition, our U-series ages agree with visual observations, indicating that while most recent volcanic activity occurs at the spreading axis, active volcanism also occurs away from the axis. Specifically, the off-axis pillow ridge and seamount samples overlying the off-axis subsurface melt body have eruption ages of less than 8 ka, and likely as young as 1 ka, despite being located on crust that has a spreading age of {\~{}}75 ka. The young ages of these lavas, combined with existing geological, geochemical and geophysical constraints, provide evidence for a genetic link between the pillow ridge and seamount lavas and the seismically imaged, underlying off-axis melt lens. This link demonstrates that off-axis volcanism does not necessarily come from a sub-axial magma body and can be sourced directly from off-axis magma bodies.
Keywords: ROV Jason (Remotely Operated Vehicle)